Fatores ambientais que influenciam a plasticidade do SNC - Oliveira, Claudia Eunice Neves de; Salina, Maria Elisabete; Annunciato, Nelson Francisco (Acta Fisiátrica, 2001)
The central nervous system (CNS) possesses a complex neural net, with highly specialized cells, making thousands of connection at every moment; these cells determine sensitivity and motor activity, translated into behavior. Following lesion, a derangement of this neural net occurs, and the CNS begins processes of reorganization and regeneration. Neural plasticity refers to the NS’s capacity to alter some of its morphological and functional properties in response to environmental changes. Analysis of the plastic aspects of the CNS, allows us to relate them to factors like among others, environmental influences, emotional condition, and cognitive level interfering direct or indirectly with CNS plasticity and the rehabilitation of the neurological patient. By searching for theoretical support, we now expect to bring basic knowledge to clinical practice and new views on the perspectives for rehabilitation of this patient.